2002
DOI: 10.1111/j.1469-8749.2002.tb00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern‐reversal visual evoked potentials in infants: gender differences during early visual maturation

Abstract: This paper investigates gender differences in the peak latency and amplitude of the P1 component of the pattern-reversal visual evoked potential (pattern-reversal VEP) recorded in healthy term infants. Pattern-reversal VEPs in response to a series of high contrast black and white checks (check widths 120', 60', 30', 24', 12', 6') were recorded in 50 infants (20 males, 30 females) at 50 weeks post-conceptional age (PCA) and in 49 infants (22 males, 27 females) at 66 weeks PCA. Peak latency of the major componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 21 publications
3
30
0
1
Order By: Relevance
“…In infants, Malcolm et al. (28) again found shorter latencies for girls, but in their study differences in head size could not entirely account for the difference observed. In the current study, there was no difference in gender distribution between SGA and AGA children, and a univariate analysis of head size on VEP latency did not reveal any effect.…”
Section: Discussionmentioning
confidence: 68%
“…In infants, Malcolm et al. (28) again found shorter latencies for girls, but in their study differences in head size could not entirely account for the difference observed. In the current study, there was no difference in gender distribution between SGA and AGA children, and a univariate analysis of head size on VEP latency did not reveal any effect.…”
Section: Discussionmentioning
confidence: 68%
“…The background may be related to various mechanisms, probably governed by sex-specific gene activation including sex hormones (see [22] for a review). Advanced CNS development in the human female sex has previously been demonstrated in terms of earlier appearing habituation to auditory stimuli (a basal form of learning) in fetuses [23], an earlier demonstrable, thicker corpus callosum in female fetuses [24] and shorter latencies of visual evoked potentials in female infants [25]. As the infraslow waves of the cortex are thought to be cortically generated [16], the findings of the present study are the first to show a sex difference of such activity in human neonates.…”
Section: Discussionmentioning
confidence: 98%
“…Another concern is the imbalance of females to males in the preterm group. Some recent studies have reported shorter P100 latencies for pattern‐reversal VEPs in females than males (Malcolm et al ., 2002; Emmerson‐Hanover, Shearer, Creel & Dustman, 1994). However, as no significant effect of gender was observed ( p = .9) when we included gender as a factor in the statistical analyses for P100 latency, we are confident that our findings are not attributable to the presence of more females than males in our preterm sample.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented smaller head circumference in preterm compared to full-term children (Peterson, Taylor, Minich, Klein & Hack, 2006), and reported that peak P100 latency was highly correlated with orbitofrontal head circumference, i.e. larger circumferences were associated with longer P100 latencies (Malcolm, McCulloch & Shepherd, 2002). However, when our circumference data were analysed according to the 'shorter P100 latency' ⁄ 'longer P100 latency' groups, no significant difference was found (p > .05), thereby arguing against the possibility that head circumference influenced our results.…”
Section: Other Possible Factors Underlying the P100 Findingmentioning
confidence: 99%